A New Galactic Wolf-Rayet Star in Centaurus. (14th September 2011) - Roman-Lopes, A.
Abstract : I communicate the detection of a new Galactic Wolf-Rayet star (WR60a) in Centaurus. The H- and K-band spectra of WR60a show strong carbon near-infrared emission lines, characteristic of Wolf-Rayet stars of the WC5-7 subtype. Adopting mean absolute magnitude MK and mean intrinsic (J - K S ) and (H - K S ) colours, it was found that WR60a suffers a mean visual extinction of3.8 ± 1.3 magnitudes, being located at a probable heliocentric distance of5.2 ± 0.8  Kpc, which for the related Galactic longitude (l = 312 ) puts this star probably in the Carina-Sagittarius arm at about 5.9 kpc from the Galactic center. I searched for clusters in the vicinity of WR60a and in principle found no previously known clusters in a search radius region of several tens arcminutes. The detection of a well-isolated WR star induced us to seek for some still unknown cluster, somewhere in the vicinity of WR60a. From inspection of 5.8  μ m and 8.0  μ m Spitzer/IRAC GLIMPSE images of the region around the new WR star, strong mid-infrared extended emission at about 13.5 arcmin south-west of WR60a was found. The study of the H-KS colour distribution of point sources associated with the extended emission reveals the presence of a new Galactic cluster candidate probably formed by at least 85 stars.